2015
DOI: 10.12681/mms.1072
|View full text |Cite
|
Sign up to set email alerts
|

A review of Italian research on free-living marine nematodes and the future perspectives on their use as Ecological Indicators (EcoInds)

Abstract: The use of free-living marine nematodes as ecological indicators (EcoInds) of human impacts has increased greatly in Italy since 1990. This paper is a summary of the Italian research experience in the study of nematode assemblages of shallow water habitats, and provides a breakdown of the most important insights that have been obtained so far. Although nematodes are among the best candidates for the Ecological Quality (EcoQ) assessment in the benthic domain, many guidelines need to be developed and limits over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 78 publications
1
27
1
Order By: Relevance
“…For example, at Falconara, characterized by the lowest levels of trophic status and of biodiversity, some indicators of ecological quality status (c-p and ITD) give "moderate" or even "good" assessment in few sampling times (Table 8B). Such discrepancies suggest the need of combined simultaneous use of a wide range of ecological indicators, coupled with indicators of trophic status, in order to achieve a reliable environmental assessment (Semprucci et al, 2015a;2015b;Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, at Falconara, characterized by the lowest levels of trophic status and of biodiversity, some indicators of ecological quality status (c-p and ITD) give "moderate" or even "good" assessment in few sampling times (Table 8B). Such discrepancies suggest the need of combined simultaneous use of a wide range of ecological indicators, coupled with indicators of trophic status, in order to achieve a reliable environmental assessment (Semprucci et al, 2015a;2015b;Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The ITD index was included in our analysis, since it still results a controversial indicator for EQS assessment. Indeed, ITD was first proposed as possible indicator and criticized after some years (Moreno et al, 2011;Semprucci et al, 2015a), since recent studies reported ambiguous influence of various stressors on ITD (Semprucci et al, 2015a;b). In this context, the ITD was included here in order to provide more information on its realibility, particularly for sites subjected to environmental multiple-stressors.…”
Section: Indicators Of Ecological Quality Based On Nematode Biodiversitymentioning
confidence: 99%
See 3 more Smart Citations